Religious Moderation Strategy in The Virtual Era and Its Implication in Improving the Quality of Education - Faisal S. Kamaludin; Tata Septayuda Purnama; Zirmansyah Zirmansyah (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2021)
Technology use in education is important to transfer knowledge and solve problems especially during the pandemic situation. Unfortunately, the development of technology has not brought the positive assurance for religious moderation discourse amongst Muslims in Indonesia. One of the risks facing students during independent online learning is that they are exposed to vulnerable and extreme radical teachings. The present study investigated the school’s strategies to safeguard religious moderation policy during online learning. It applied qualitative method using case study. The findings show the application of religious moderation strategies have brought positive impact on educational quality. The strategies required cooperation among several parties including teachers, students, parents. Their strategic partnership is pivotal element to increase educational quality